Ilulissat Icefjord, Greenland Iceberg Positional Data and Expendable Conductivity-Temperature-Depth (XCTD), August 2014 and 2019 ... - Baratta, Sydney; Schild, Kristin; Sutherland, David (NSF Arctic Data Center, 2023)
This dataset is comprised of on-iceberg Geographic Positioning System (GPS) data, The Expendable Conductivity/Temperature/Depth (XCTD) and Conductivity, Temperature, and Depth(CTD) oceanographic data, iceberg surface three dimensional (3D) point clouds, constructed using structure from motion (SFM) of drone imagery. Data were collected during the late-summers of 2014 and 2019 in Ilulissat Icefjord, West Greenland. Processing methods for these data are explained in the manuscript 'Ilulissat Icefjord Upper-Layer Circulation Patterns Revealed through GPS-Tracked Icebergs ' by Sydney J.N. Baratta, Kristin M. Schild, and David A. Sutherland. The abstract and plain language summary for that paper are included below. Abstract The Greenland Ice Sheet has undergone rapid mass loss over the last four decades, primarily through solid and liquid discharge at marine-terminating outlet glaciers. The acceleration of these glaciers is in part due to the increase in temperature of ocean water in contact with the glacier ...